2020
DOI: 10.1007/978-3-030-45712-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Susceptibility Measures to Persuasion

Abstract: There is increasing evidence that indicates how personalising persuasive strategies may increase the effectiveness of persuasive technologies and behaviour change interventions. This has led to a wide range of studies exploring susceptibility to persuasion which highlight the role of individual differences. Measuring susceptibility to persuasion, while accounting for individual differences can be challenging, particularly where persuasive strategies may be considered similar due to their underlying components.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Oyibo et al’s findings support the results illustrated in Figure 3 since the majority of participants in this study are from individualist continents (as shown in Table 3 ). Also, a recent study by Vargheese et al (2020) confirms these findings. Vargheese et al stated that there is no actual relationship between the effectiveness of persuasive strategies and the ages of participants.…”
Section: Data Analyses and Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Oyibo et al’s findings support the results illustrated in Figure 3 since the majority of participants in this study are from individualist continents (as shown in Table 3 ). Also, a recent study by Vargheese et al (2020) confirms these findings. Vargheese et al stated that there is no actual relationship between the effectiveness of persuasive strategies and the ages of participants.…”
Section: Data Analyses and Resultssupporting
confidence: 58%
“…Besides, the authors found a significant difference between males and females in terms of Authority , where males found to be more persuadable. Vargheese et al (2020) also found that the effectiveness of the persuasive principles does not differ based on the gender of the participants.…”
Section: Data Analyses and Resultsmentioning
confidence: 79%
“…Specifically, we leverage Petty and Cacioppo's elaboration likelihood model ( 1986) and Chiaken's social information processing model (Chaiken 1980), which suggest that people process information in two ways: either performing a relatively deep analysis of the quality of an argument or relying on some simple superficial cues to make decisions (Cialdini 2001). Guided by these psychology insights, we examine the aforementioned computational studies on persuasion and argumentation (Wang et al 2019;Yang et al 2019;Durmus, Cardie, and Durmus 2018;Vargheese, Collinson, and Masthoff 2020a;Carlile et al 2018), and further synthesize these theoretical and practical tactics into eight unified categories: Commitment, Emotion, Politeness, Reciprocity, Scarcity that allow people to use simple inferential rules to make decisions, and Credibility, Evidence, Impact that require people to evaluate the information based on its merits, logic, and importance. As shown in Table 1, our taxonomy distilled, extended, and unified existing persuasion strategies.…”
Section: Persuasion Taxonomy and Corpusmentioning
confidence: 99%